A new species of Neoconidiobolus (Entomophthorales, Ancylistaceae) from China based on morphological, molecular and physiological evidences - Nie, Yong; Wang, Zi-Min; Zhou, Zheng-Yu; Zhao, Heng; Liu, Xiao-Yong; Huang, Bo (Phytotaxa, 2022)
Neoconidiobolus pseudothromboides is proposed as a species new on the basis of morphological characteristics, physiological feature and molecular phylogeny. This new species is morphologically allied to N. thromboides. However, the maximum growth temperature of this new species is lower than that of N. thromboides and it grows slower than N. thromboides. The phylogenetic analysis of mitochondrial small subunit (mtSSU), nuclear large subunit (nucLSU) and translation elongation-factor-like (EFL) reveals that Neoconidiobolus is divided into three clades, and N. pseudothromboides sp. nov. is closely related to N. lachnodes rather than N. thromboides. Morphological comparisons between N. pseudothromboides sp. nov. and its affinities are provided herein.